2019
DOI: 10.1103/physrevd.100.124057
|View full text |Cite
|
Sign up to set email alerts
|

Thick brane in reduced Horndeski theory

Abstract: Horndeski theory is the most general scalar-tensor theory retaining second-order field equations, although the action includes higher-order terms. This is achieved by a special choice of coupling constants. In this paper, we investigate thick brane system in reduced Horndeski theory, especially the effect of the non-minimal derivative coupling on thick brane. First, the equations of motion are presented and a set of analytic background solutions are obtained. Then, to investigate the stability of the backgroun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…[59][60][61] and also, in the case of braneworld scenarios with bulk fluids parametrized by a nonlinear equation of state [62]. Moreover, the Horndeski theory and related generalizations provide interesting possibilities to study scalartensor theories of generalized gravity [63] and this adds more motivation to study braneworld issues within the Horndeski scenarios [64]. These and other related issues are now under investigation and we hope to report on them in the near future.…”
Section: Comments and Conclusionmentioning
confidence: 99%
“…[59][60][61] and also, in the case of braneworld scenarios with bulk fluids parametrized by a nonlinear equation of state [62]. Moreover, the Horndeski theory and related generalizations provide interesting possibilities to study scalartensor theories of generalized gravity [63] and this adds more motivation to study braneworld issues within the Horndeski scenarios [64]. These and other related issues are now under investigation and we hope to report on them in the near future.…”
Section: Comments and Conclusionmentioning
confidence: 99%
“…Regarding the performance of MGGA functionals implemented with a non-multiplicative potential, a certain number of results are available for ferromagnetic metals. 95,[234][235][236][237][238][239][240] From these studies the most interesting results concern the SCAN functional, which has been shown to overestimate the magnetic moment, and sometimes by a rather large amount (e.g., ∼ 0.5 µ B for Fe). However, such overestimation is not systematically observed with functionals of this class, since other MGGA functionals like TPSS 163 or revTPSS 164 lead to values similar to PBE.…”
Section: Magnetismmentioning
confidence: 99%
“…However, such overestimation is not systematically observed with functionals of this class, since other MGGA functionals like TPSS 163 or revTPSS 164 lead to values similar to PBE. 95,234,239 In summary, the standard LDA and GGA lead to magnetic moments which are qualitatively correct for itinerant metals, but not for AFM solids with strongly correlated electrons (strong underestimation). On the other hand, methods giving much more reasonable magnetic moments in AFM solids, e.g., mBJLDA, GLLB-SC, or HSE06, lead to strong overestimation in itinerant metals.…”
Section: Magnetismmentioning
confidence: 99%
“…[1] For instance, DNA alkylation is generally unavoidable due to the abundant presence of alkylating agents in the environment as bypass products of biological and industrial processes but also inside the living cells as byproducts of oxidative damage or from cellular methyl donors. [2] Despite the fact, that alkylating agents can induce cancer, many of them are commonly used as anticancer drugs. The predominant adducts formed by alkylating agents in DNA are N7-methyl-dG, N3methyl-dA, and O6-methyl-dG.…”
Section: Introductionmentioning
confidence: 99%